Tourism and Referral Healthcare System Efficiency the Role of Sustainability and Socio-Cultural Factors in Uttar Pradesh - Gupta, Sonika; Srivastava, Alpana; Mishra, Bharat; Mishra, Manish; Bajpai, Varun (International Review of Management and Marketing, 2025)
Medical tourism has become a rapidly expanding sector that intersects healthcare and hospitality, enabling patients to travel across borders for specialized, high-quality, and cost-effective treatments. In India, Uttar Pradesh is emerging as a competitive medical tourism destination, supported by its expanding network of tertiary and referral healthcare facilities. This study investigates the influence of medical tourism, sustainability practices, socio-cultural factors, and infrastructure and operational capacity on the efficiency of referral healthcare systems in the state. A quantitative, cross- sectional research design was employed, using a structured questionnaire administered to 372 patients and caregivers who had accessed referral services within the past 12 months. Data were analyzed using structural equation modeling (SmartPLS 4). The results reveal that infrastructure and operational factors, medical tourism, and socio-cultural factors have significant positive effects on referral healthcare system efficiency, while sustainability practices show a positive but statistically insignificant relationship. The findings extend the literature by integrating healthcare operations, hospitality management, and socio-cultural competence into a unified analytical framework. Managerial and policy implications include prioritizing infrastructure enhancement, institutionalizing cultural competence training, and embedding operational improvements into medical tourism strategies. The study also highlights the need for more systematic integration of sustainability practices into hospital operations to translate long-term ethical commitments into measurable operational outcomes.